Integrated Approach to Explore Multidimensional Urban Morphology of Informal Settlements: The Case Studies of Lahore, Pakistan - Arif, Muhammad Mashhood; Ahsan, Muhammad; Devisch, Oswald; Schoonjans, Yves (MDPI, 2022)
The understanding of urban morphology as a means of exploring the materiality of urban areas has been an emerging practice amongst academics, but the reach of the methods in urban-design research has been limited. This research presents the integration of GIS application and fieldwork analysis as the main methods to support the interpretation of urban morphology as methodical, exploratory, and multidimensional. The Kolmogorov-Smirnov test, commonly known as the KS test, is also conducted to illustrate a contrast among the settlements. The study focuses on various dimensions of informal settlements by drawing on three case studies of informal settlements in Lahore, Pakistan. The results show heterogeneity in the urban form in terms of land-use diversity, building density, connectivity, open-space ratio, and infrastructural quality within the case-study areas. The analysis displays the context sensitivity and diversity within these settlements that provide a better understanding of how informal settlement works in relation to urban morphology. This research has the characteristics to contribute to other urban-form studies through the coherent application of the procedures to various sites. The output of mixed-use techniques exercised in this study lends itself to integration with other systematic processes related to urban areas' design, research, and planning.
Keywords: spatial structure; built form; informal urbanism; mapping; urban morphology; upgrading; urbanity; GIS; SLUM; RESILIENCE; CITY; Science & Technology - Other Topics; Environmental Sciences & Ecology